The Divided Globalization of Social Sciences in an Unequal World and Anti - Concepts - Raina Zimmering (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2025)
In this analysis of critical political science in the framework of the entanglement between post structural and ontological approaches, the author goes beyond the usual claims by asserting that since globalization, especially in the economic and political domains, is not a uniform and integrated process, likewise the globalization of social sciences does not necessarily enhance cooperation and promote equal participation. First, there is a process of standardization of the social sciences through international criteria of peer reviewing and ranking, the so called Social Science Citation Index - SSCI. These are common and universal criteria for evaluating research products by experts claiming to be neutral-which suggests the imposition of a kind of scientific imperialism. However, going against this mainstream is the emergence of scientific networks on the internet representing different universities and research institutes highlighting the works especially of young researchers, not to mention the many forums on the internet affiliated with various international scientific societies, associations and federations all over the world. There are attempts to change the course of the current “imperialist” globalization of social sciences from the Global North in developing a “scientific life” from the bottom based on participative principles in alternative autonomous spaces, for example the rebellious Zapatistas communities in Mexico. This is something quite new and has yet to be developed further. Received 15th March 2018; Revised 9th October 2018; Accepted 20th October 2018